Health Disparities in Rheumatology in the United States - Wright GC; Zueger PM; Copley-Merriman C; Khan S; Costello J; Krumbach A; Reddy P; Tanjinatus O; Wells AF (Open Access Rheumatology: Research and Reviews)
Grace C Wright,1 Patrick M Zueger,2 Catherine Copley-Merriman,3 Shahnaz Khan,4 Jessica Costello,5 Alisha Krumbach,3 Priya Reddy,1,6 Oishi Tanjinatus,7 Alvin F Wells8 1Association of Women in Rheumatology, New York, NY, USA; 2Health Economics and Outcomes Research, AbbVie Inc, North Chicago, IL, USA; 3Value & Access, RTI Health Solutions, Ann Arbor, MI, USA; 4Value & Access, RTI Health Solutions, Research Triangle Park, NC, USA; 5Value & Access, RTI Health Solutions, Didsbury, Manchester, UK; 6US Medical Affairs Rheumatology, AbbVie Inc, North Chicago, IL, USA; 7Southwest Florida Rheumatology, Riverview, FL, USA; 8Advocate Health Medical Group, Franklin, WI, USACorrespondence: Grace C Wright, Association of Women in Rheumatology, 345 E 37th St, Suite 303C, New York, NY, 10016, USA, Tel +1 212-490-6960, Fax +1 212-490-6966, Email gcwright.md@gmail.comObjective: Underserved populations are often at risk of experiencing systematic healthcare disparities. Existing disparities in care access, quality of care received, and treatment outcomes among patients with rheumatic disease are not well understood.Methods: We conducted a targeted literature review to understand disparities in health outcomes, treatment patterns, and healthcare management faced by rheumatology patients in the United States, with a focus on rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS).Results: The findings of this review indicate that disparities in RA, PsA, and AS affect several historically underserved populations, including underrepresented racial and ethnic groups, persons with lower socioeconomic status (SES), persons experiencing homelessness, and patients with Medicare or Medicaid insurance types. The disparities experienced by these populations include greater disease activity and severity, decreased or delayed access to specialist care, decreased likelihood of receiving advanced therapeutics, and worse clinical outcomes.Conclusion: To provide equitable healthcare for all patients with RA, PsA, and AS, multiple closely linked health disparities must be addressed. Possible solutions include partnerships between healthcare systems and community-based organizations, targeted outreach tailored to patients with low SES, interventions to improve patient adherence and knowledge, and interventions to improve access to care for rural-residing and unhoused patients. In all, the findings of this literature review underscore the need for mitigation of health disparities in rheumatology care and may serve as a foundation for developing strategies to reduce disparities.Keywords: Healthcare disparities, health inequities, rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, United States, social determinants of health